Transfer Informasi Intra Industri di Sekitar Pengumuman Dividen - Emilia Frida Yusnitasari (The Indonesian Journal of Accounting Research, 2013)
Investors in companies in the same industry as the announcing firm do extrapolate information from the announcement to make inferences about industry-wide economic prospects. The purpose of this study is to examine empirically transfer information intra-industry around reporter’s dividend changes announcement that is indicated by abnormal return of nonreporter firm. This study used sample of 90 nonreporter for dividend decreased and 82 nonreporter for dividend increased during 1994-1996 time periods. The statistic methods used to test hypothesis are t-test and multiple regression analysis.The result of the study shows that dividend change announcement having informational value for other firms in the same industry as dividend reporter. Further, there is competitive effect for dividend-decreased announcement. That is dividend decreased reporter is reacted positively by nonreporter. While for dividend-increased announcement, there is contagion effect. Nonreporter react positively or the same direction as the reporter’s reaction. Another finding show that the magnitude of dividend change, size of nonreporter firm couldn’t explain the magnitude of the transfer information.